Approach to Discursive Incidents in the Spanish Investiture Debate (Spain, January 4, 2020) - Ouahmane, Abderrahim (2024)
In parliamentary sessions, there are some incidents and actions issued by some deputies who were not given the floor to speak. The calls for attention from the presidency of Congress, the protests of deputies or other non-verbal actions such as applause, rumors, or laughter, involve practices that may affect the communicative purpose of the speaker. The issuance of these incidents is motivated by certain elements that promote them. This article analyzes the interventions made by the presidents of the four most voted forces in Spain, on the occasion of the investiture debate that took place in the Congress of Deputies on January 4, 2020 (Cortes Generales, 2020). In a context of political turmoil, party leaders raised the speeches to get their messages across clearly and convincingly. The analysis intends to detect, identify the discursive incidences that our corpus registers, especially in its forms of appearance.